Medical Errors and Patient Safety as Perceived by Nurses - Raseel Shuja Alghamdi, Alaa Madani Ahmed Alshareef, Zahra Sonbol hadi Mubarak, Renad Abdulaziz Alowayshiq, Norah khaleed alarfaj, Meaad khalaf olewe alenazi, Ayidh Mohammed salem AlRasheed, Maryam Saeed Jazi Alrefaei; Yossra Mohammad Ali Abueisa, Yasameen Salamah Alrefaei, Amna yahia Abdullah Sufiany, Rajaa Ali Hassan Gharawi (International Journal of Medical Toxicology and Legal Medicine, 2024)
A worldwide issue, patient safety is a crucial component of the caliber of health care systems. One of the main risk factors for medical mistakes that compromise patient safety is the human element. In order to investigate how this element affects patient safety in the hospitals in the Saudi Arabian city of Ha’il, nurses’ views of the categories of respondents’ characteristics in relation to risk factors were evaluated using the ANVOA (One Way). At P<0.05, significant differences were found between the study sample’s demographic features and the human resources risk variables that contribute to medical errors.